1999
DOI: 10.1094/mpmi.1999.12.8.712
|View full text |Cite
|
Sign up to set email alerts
|

A Bean cDNA Expressed During a Hypersensitive Reaction Encodes a Putative Calcium-Binding Protein

Abstract: The hypersensitive reaction (HR) is an inducible plant response that is associated with disease resistance. It is characterized by rapid, localized cell death at the site of infection and is believed to inhibit the spread of invading pathogens. We have isolated a cDNA clone, designated Hra32 (for hypersensitive reaction associated), corresponding to an RNA transcript that accumulates in bean during an HR. The predicted protein product of the Hra32 cDNA is an approximately 17 kDa protein of 161 amino acids, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…glycinea (18); and (vi) pooled bean leaf tissue undergoing hypersensitive response as a result of infiltration of Pseudomonas syringae pv. tabaci Pt11528 (19).…”
Section: Materials-easymentioning
confidence: 99%
“…glycinea (18); and (vi) pooled bean leaf tissue undergoing hypersensitive response as a result of infiltration of Pseudomonas syringae pv. tabaci Pt11528 (19).…”
Section: Materials-easymentioning
confidence: 99%
“…Although herbivory damage usually concerns aphid or caterpillar attack, the generation of wound responses could be the same after cattle or sheep damage. Plant parts damaged by herbivory can produce a systemic wound response, localized proteolysis and necrosis (Jakobek et al, 1999 ;Rhodes et al, 1999 ;Suh et al, 1999). The response to wounding in detached plant parts might differ from that observed in intact plant parts.…”
Section: Wounding Responses\pathogen Attachmentmentioning
confidence: 99%
“…In the field, plants are exposed to a variety of potentially pathogenic microorganisms and have developed species-specific degrees of tolerance and resistance (Greenberg, 1997 ;Morel & Dangl, 1997). The hypersensitive response can be generated in vitro by incubation of plant material with 10& cells ml −" of bacteria, with lesions appearing after 72 h (Jakobek et al, 1999). The observation that hypersensitive cell death does not occur in cell cultures (Honee et al, 1998) could be interpreted to dismiss the significance of hypersensitive response in plant tissue in the rumen.…”
Section: Wounding Responses\pathogen Attachmentmentioning
confidence: 99%
“…Red Kidney) leaf tissue undergoing an HR after infiltration with P. syringae pv. tabaci Pt11528 (Jakobek et al, 1999). This library was screened as previously described (Jakobek et al, 1999) using a combination of differential and cold-plaque screening to identify cDNAs corresponding to transcripts expressed during an HR.…”
mentioning
confidence: 99%
“…tabaci Pt11528 (Jakobek et al, 1999). This library was screened as previously described (Jakobek et al, 1999) using a combination of differential and cold-plaque screening to identify cDNAs corresponding to transcripts expressed during an HR. During this process a cDNA clone, designated Hra28 (for hypersensitive reaction associated), was identified that is predicted to encode a novel acid phosphatase (GenBank Accession No.…”
mentioning
confidence: 99%